Activation of the alternative complement pathway by a streptococcal lipoteichoic acid. - Fiedel, B A (1978)
A glycerol lipoteichoic acid antigen from Streptococcus pyogenes 1-RP41 was found by rabbit erythrocyte hemolytic assay to activate the alternative complement pathway in human sera. Over a narrow concentration range of the teichoic acid, complement consumption was dose dependent, whereas at higher concentrations of the acid complement consumption could not be detected.